Has the Euro changed the Business Cycle? - Zeno Enders; Philip Jung; Gernot J. Müller (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
In this paper we analyze European business cycles before and under EMU. Across the two periods we ?nd 1) a signi?cant decline in real exchange rate volatility, 2) signi?cant changes in cross-country correlations, and 3) the volatility of macroeconomic fundamentals largely un- changed. We develop a two-country business cycle model and show that the calibrated model is able to replicate key features of the data prior to and under EMU.We ?nd that the euro has a strong bearing on the transmission mechanism as cross-country spillovers increase substantially under EMU. As a result, foreign shocks become more and domestic shocks less important in accounting for the (unchanged) volatility of macroeconomic fundamentals.
Keywords: F41; F42; E32; 330; European business cycles; Euro; Optimum Currency Area; EMU; Monetary Policy; Exchange rate regime; Cross-country spillovers; Konjunktur; Volatilität; Europäische Wirtschafts- und Währungsunion; Konjunkturzusammenhang; Schock; Spillover-Effekt; EU-Staaten